2011
DOI: 10.1074/jbc.m111.253328
|View full text |Cite
|
Sign up to set email alerts
|

Phage Display of Tissue Inhibitor of Metalloproteinases-2 (TIMP-2)

Abstract: Tissue inhibitor of metalloproteinases-2 (TIMP-2) is a broad spectrum inhibitor of the matrix metalloproteinases (MMPs), which function in extracellular matrix catabolism. Here, phage display was used to identify variants of human TIMP-2 that are selective inhibitors of human MMP-1, a collagenase whose unregulated action is linked to cancer, arthritis, and fibrosis. Using hard randomization of residues 2, 4, 5, and 6 (L1) and soft randomization of residues 34 -40 (L2) and 67-70 (L3), a library was generated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…In related work from the same laboratory, phage display was utilized with TIMP-2 to identify selective inhibitors of MMP-1 [99]. Three regions of TIMP-2 underwent randomization, residues 2–6 (excluding residue 3), 34–40, and 67–70.…”
Section: Inhibitors Of Matrix Metalloproteinasementioning
confidence: 99%
“…In related work from the same laboratory, phage display was utilized with TIMP-2 to identify selective inhibitors of MMP-1 [99]. Three regions of TIMP-2 underwent randomization, residues 2–6 (excluding residue 3), 34–40, and 67–70.…”
Section: Inhibitors Of Matrix Metalloproteinasementioning
confidence: 99%
“…While many studies have demonstrated that TIMPs can signal through a number of important regulatory pathways, there is currently little information regarding how TIMP proteins actually function in vivo, particularly as their domains may act through both MMP-dependent and -independent mechanisms (Stetler-Stevenson 2008a). Accordingly, in this study we examined the individual domains of TIMP-2 and -3 in early stage X. laevis embryos to gain an understanding of how the individual N-and C-terminal domains may regulate key developmental events as there is evidence that TIMP N-and C-terminal domains may have unique properties and can function independently as individual domains (Bahudhanapati et al 2011;Brew and Nagase 2010;Chirco et al 2006) and maintain their native topology (Wu et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This activity is thought to occur through the TIMP C-terminal domains and is independent of their MMP-inhibitory activity, which occurs exclusively at the N-terminus (DeClerck et al 1993;Nagase et al 2006). The 2 domains of TIMPs are thought to have evolved separately, and both domains have the ability to fold and function independently, as demonstrated with Nterminal domain expression in heterologous systems that still maintains a stable native structure, and can act as an MMP inhibitor (reviewed in Brew and Nagase 2010;Bahudhanapati et al 2011). …”
Section: Introductionmentioning
confidence: 97%
“…Based on our structural analyses, we suggest that peripheral epitopes, presented not only by the AB loop but also by the C-terminal domain of the TIMP scaffold, might be more intensively targeted for optimization to enhance inhibitor selectivity toward individual MMPs. Such efforts could take advantage of diversity library screening and directed evolution, such as the phage display approach recently successful in identifying an MMP-1-selective variant of TIMP-2 [60]. Ultimately, continued efforts to understand and exploit the structural basis of molecular recognition of MMPs by TIMPs may facilitate development of new MMP-directed probes and therapeutics, taking advantage of emerging concepts for delivery of TIMP-based drugs and probes in vivo [61], [62], [63].…”
Section: Discussionmentioning
confidence: 99%